Sagittal Balance Concept and Spinopelvic Parameters - Sadeghian, Mohammad; Golbakhsh, Mohammadreza; Rahimian, Abbas; Talebiyan, Parham; Dehghani Firoozabadi, Mohammad Javad (Journal of orthopedic & spine trauma, 2023)
“Sagittal balance” is defined by the anatomic relationship between the pelvis and the spine in the sagittal plane to keep the center of gravity over the feet. It is important to calculate the anatomical parameters of cervical, thoracic, lumbar, and spinopelvic regions and how any static and dynamic changes could affect the sagittal balance to understand the conditions necessary for such a balance. One of the effective changes in sagittal balance is aging, which leads to changes in spine parameters and further activation of compensatory mechanisms. Understanding the relationships between these parameters, especially in pathological cases, helps correct spine sagittal imbalance.